GENES, CELLS AND BRAINS : THE PROMETHEAN PROMISES OF THE NEW BIOLOGY - HILARY ROSE; STEVEN ROSE (LONDON FOUNDATION BOOKS, 2015)
Examining the establishment of biobanks, the rivalries between public and private genesequencers, and the rise of stem cell research, the authors ask why the promised cornucopia of health benefits has failed to emerge and reveal the questionable enterprise that has grown out of bioethics. The human body is becoming a commodity, and the unfulfilled promises of the science behind this revolution suggest profound failings in genomics itself.
Keywords: BIOENGINEERING; GENOMICS-SOCIAL ASPECTS; BIO ETHICS